2020
DOI: 10.1021/acs.analchem.0c04047
|View full text |Cite
|
Sign up to set email alerts
|

Isothermal Amplification and Ambient Visualization in a Single Tube for the Detection of SARS-CoV-2 Using Loop-Mediated Amplification and CRISPR Technology

Abstract: We have developed a single-tube assay for SARS-CoV-2 in patient samples. This assay combined advantages of reverse transcription (RT) loop-mediated isothermal amplification (LAMP) with clustered regularly interspaced short palindromic repeats (CRISPRs) and the CRISPR-associated (Cas) enzyme Cas12a. Our assay is able to detect SARS-CoV-2 in a single tube within 40 min, requiring only a single temperature control (62 °C). The RT-LAMP reagents were added to the sample vial, while CRISPR Cas12a reagents were depos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
162
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 192 publications
(163 citation statements)
references
References 38 publications
0
162
0
1
Order By: Relevance
“…[12][13][14] Among the many applications, CRISPR-Cas systems have been incorporated into the development of rapid POC diagnostic tests for the coronavirus disease of 2019 (COVID-19). [15][16][17][18] The potential of CRISPR technology in high-throughput and comprehensive diagnostics of multiple viral infections has recently been demonstrated. 19 In this review, we highlight how unique features of CRISPR-Cas systems are integrated with innovative nucleic acid amplication techniques, including amplication of the target and the signal, to achieve sensitive and specic detection of nucleic acids, proteins, and small molecules.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] Among the many applications, CRISPR-Cas systems have been incorporated into the development of rapid POC diagnostic tests for the coronavirus disease of 2019 (COVID-19). [15][16][17][18] The potential of CRISPR technology in high-throughput and comprehensive diagnostics of multiple viral infections has recently been demonstrated. 19 In this review, we highlight how unique features of CRISPR-Cas systems are integrated with innovative nucleic acid amplication techniques, including amplication of the target and the signal, to achieve sensitive and specic detection of nucleic acids, proteins, and small molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Real-time reverse transcription polymerase chain reaction (RT-PCR) as the most wide detection method has made tremendous contributions to the epidemic prevention and control of COVID-19 since the SARS-CoV-2 genome sequence was released ( Corman et al, 2020 ). However, some technical shortcomings such as long processing time, laborious, involving specialized instruments, skilled personnel and insurmountable false negatives encourage the further efforts to develop more reliable diagnosis systems for thoroughly screening of suspicious patients ( Ali et al, 2021 ; Baek et al, 2020 ; Pang et al, 2020 ; Zhu et al, 2020 ). Electrochemical biosensors are considered to be one of the most powerful alternative tools for the real-time monitoring of COVID-19 in the clinical diagnosis ( Ji et al, 2020 ; Mahshid et al, 2021 ), for instance, Chaibun et al have reported a rapid electrochemical biosensor for detection of SARS-CoV-2 RNA as low as 1 copy/μL within 2 h, showing its high sensitivity, rapidity and robustness ( Chaibun et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The present method has the advantage of combining two assays without RNA extraction, which, in our hands gives a more robust result that either one separately, as it is more sensitive and specific, while conserving specific technical benefits useful for deploying in the daily lab. For example, the recently published Pang et al method ( 14 ) uses the same tube for the reaction but requires previous RNA extraction and a higher level of manipulation, since each tube has to hold the Cas12 mix in the lid, which is prone to errors when working with multiple samples. The recently published assay by Lalli et al ( 15 ) does not need previous RNA isolation, but starts with saliva, which, in our hands at least, have a reproducibility and specificity issues, as we have found that the additional use of Cas12a decrease false positives.…”
Section: Discussionmentioning
confidence: 99%